Understanding the politics of pandemic scares : an introduction to global politosomatics - Aaltola, Mika. (New York : Routledge, 2012)
'Reactions to pandemics are unlike any other global emergency; with an emphasis on withdrawal and containment of the sight of the infected. Dealing with the historical and conceptual background of diseases in politics and international relations, this volume investigates the global political reaction to pandemic scares. By evaluating anxiety and the political response to pandemics as a legitimisation of the modern state and its ability to protect its citizens from infectious disease, Understanding the Politics of Pandemic Scares examines the connection between international health governance and the emerging Western liberal world order. The case studies, including SARS, Bird Flu and Swine Flu, provide an understanding of how the world order, global health governance and people's bodies interact to produce scares and panics. Aaltola introduces an innovative new concept of'politosomatics' based on the relationship that links individual stress, strain, and fear with global circulations of power to evaluate increasingly global bio-political environments in which pandemics exist. This book will be of interest to students and researchers of International Relations, Global Health, International Public Health and Global Health governance'--
1. Introduction -- 2. Containments and compassions of pandemic dramas -- 3. Understanding the vortex of war and disease -- 4. Trajectory of a pandemic drama : ebbing and waning of the BSE crisis in 1996 -- 5. Vortexes of SARS : anxieties over global air mobility -- 6. The pandemic geography of avian flu -- 7. Beyond global public health.
Includes bibliographical references : (p. [194]-205) and index.
Mode of access : World Wide Web.
Keywords: Communicable diseases -- Political aspects; World politics -- Psychological aspects; World health; Health behavior